Electoral participation in Iceland of the youth, generational gap, political interest and party identification - Halldórsson, Eiríkur Búi; Önnudóttir, Eva Heiða (Veftímaritið Stjórnmál og stjórnsýsla, 2019)
This paper is about electoral participation in national elections in Iceland, where we analyze whether there has been a generational change in participation where younger cohorts are less likely to vote throughout their lives compared to young people before. We distinguish between age, period and cohort effect on electoral participation, using data from the Icelandic National Election Study and we find that the youngest generation today is less likely to vote compared to earlier younger generations. We discuss and analyze whether those changes can be explained by a change in political interest and party identification of younger voters. Our findings point to that the youngest generation today is just as interested in politics as young people was before and as older voters are. Political interest among younger voters has not changed and it motivates young and old people to vote in a similar way as before. We do find that party identification is today a weaker motivator for young people to vote than it was before. This, together with that political interest has not changed, could indicate that the youngest generation is more inclined to participate in politics by other ways than voting. However, it cannot be excluded that the change in voting patterns of the youngest generation is due to a delay in their maturation, meaning that today they are older when they start to take an active part in the society. Í þessari grein er fjallað um kosningaþátttöku í Alþingiskosningum á Íslandi og greint hvort að um mögulega kynslóðabreytingu sé að ræða, þar sem ungt fólk í dag tekur síður þátt í kosningum samanborið við ungt fólk áður fyrr. Notuð eru gögn úr Íslensku kosningarannsókninni og þegar áhrif aldurs, tíma og kynslóða eru aðgreind benda niðurstöður greinarinnar til þess að orðið hafi slík kynslóðabreyting. Fjallað er um hvort að þessa breytingu megi mögulega rekja til minni áhuga yngstu kynslóðar samtímans á stjórnmálum eða minnkandi flokkshollustu samanborið við ungt fólk áður fyrr. Helstu niðurstöður eru að áhugi ...